Strategi Pengembangan Ekowisata di Kawasan Waduk Pembangkit Listrik Tenaga Air (PLTA) Koto Panjang Kabupaten Kampar (Dinamika Lingkungan Indonesia, 2014)
The aims of this study are to determine the general condition of the HydroelectricDam area at Koto Panjang as a tourism , analyzing the potential of ecotourism to support theuse of Hydroelectric dam Koto Panjang and formulate the ecotourism development strategyof hydroelectric dam Koto Panjang by using descriptive qualitative method. The studyinvolved 76 people consist of 30 local people, 30 tourists , 6 businesses, and 10 officialsassociated with the utilization of hydroelectric dam Koto Panjang, to obtain the informationfrom the society in the hydroelectric dam area of Koto Panjang and from the tourist wasdistributed the questioners Randomly. The study was conducted from April to October 2012 atKampar regency that divided in several related institutions at Kampar Regency and in thePekanbaru city. The object and appeal of ecotourism that was potential to developed in thehydroelectric dams area at Koto Panjang were : 1) Dam with beautiful scenery floating netcages and small islands located in the dam, with fishing, boating, swimming, eating at afloating restaurant and watching the unloading of fish cages, 2) Deer Lake was located on thebanks of the dam with beautiful scenery, equipped playground for children that used as amotocross arena, 3) Aquari Beach was in the middle of the dam has a beautiful view of thewater tourism activities such as jet skis and canoes, and also the venue to routine cultureevent, Balimau Kasai. 4) The Peak Panorama was transitory (resting area) and strategicallylocated at the cross-roads between provinces with the very beautiful scenery towards the dam.5) Ketangka island has a gently sloping coastal island which overlooking the dam withbeautiful scenery was very suitable to be developed as a tourist hiking, camping, fishing,swimming and boating. 6) First bridge across the province road were on used to be atransitory because of the beautiful scenery under the bridge which was the dam with floatingnet attraction. The ecotourism development strategies in the hydroelectric Dam, KotoPanjang were: 1) Keeping our environment by setting zoning conservation and zoningdesignation of the activities in the dam, through the dam area authorities were authorized todetermine the rules.2)Conducting a variety of cultural events and activities in thehydroelectric Dam area, Koto Panjang which supported the availability of sufficient financialresources to completing the infrastructure. 3) Increasing the government's commitment toestablish authorities of hydroelectric dam area, Koto Panjang. 4) Implementing theRegulation in the Ecotourism area by involving the local communities, it supported by thefinancial support to completed adequate facilities and infrastructures, thus attracted touriststo open up new business opportunities for the local community.